Application of BSF Larvae Method in Solid Waste Management in the Puri Cipageran Market, Cimahi, Indonesia - Anni Rochaeni; Eki Baihaki; Cartono Cartono; Mimi Halimah; Yonik Meilawati Yustiani; Riana Saputra; Dede Sulaeman; Bryan Yogi; Ihsanul Fiqri (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
Puri Cipageran Indah (PCI) I market waste in Cimahi City is currently not managed by implementing local reduction and processing. Currently, waste is only collected and transported to the nearest TPS, without sorting and processing. There is a desire from local RW managers to do better waste management. Currently, there are around 108 traders in the market area, which only operate from 06.00-10.00 and in the afternoon for culinary traders. There is land for processing which is very limited in size (3×2 m) so that the processing technology that can be applied is also limited. One technology that can be applied is the processing of organic waste using Black Soldier Flies (BSF) larvae. Activities are carried out by holding meetings and mutual agreements regarding the layout of sanitation facilities including waste management. The provision of training to process waste using BSF larvae (maggot) was also carried out. The construction of facilities and environmental improvements are coordinated directly by partners by following the results of the agreement and research results regarding the waste processing process using maggot. In general, the activity went well, residents of PCI I Housing represented by the PCI Forum stated that they were greatly helped by the arrangement of the market area to be better and with educational nuances for the general public.